Students' analysis literacy and numeracy in linear algebra: A comparison across personality types - Wulandari Wulandari; Aklimawati Aklimawati; Erna Isfayani; Cut Morina Zubainur; Elizar Elizar; Yeni Listiana (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The imperative drives this research endeavour for educators to comprehend the diverse personality types exhibited by students. It is crucial as each personality type encompasses unique strengths and weaknesses that influence cognitive processes, decision-making, literacy, and numeracy skills. The primary objective of this study is to assess the literacy and numeracy skills of students categorized into sanguine, melancholic, choleric, and phlegmatic personality types within the context of Linear Algebra courses. Employing a descriptive research design with a qualitative approach, the subjects of this investigation comprised 47 students enrolled in the Education Mathematics Major at Malikussaleh University: the research employed personality type tests, literacy and numeracy tests, and interviews as the assessment instruments. The data analysis techniques followed the framework proposed by Miles and Huberman that involved stages such as data collection (including students' personality and literacy numeracy test results), data reduction (highlighting key elements), data presentation (displaying test and interview data), and concluding. The findings revealed that (1) 8 individuals (17.02%) exhibited a choleric personality type, eight individuals (17.02%) demonstrated a melancholic personality type, 16 individuals (34.05%) displayed a phlegmatic personality type, and 15 individuals (31.91%) manifested a sanguine personality type; (2) students' literacy and numeracy skills averaged 78.6%, falling into the high category; (3) The phlegmatic personality type exhibited the lowest literacy and numeracy ability, while the sanguine personality type demonstrated the highest literacy and numeracy ability. Consequently, this underscores the importance of students leveraging their strengths and addressing the weaknesses associated with their respective personality types to refine their literacy and numeracy skills.